The Influence Of Work Discipline, Leadership Style, And Training On Employee Performance With Job Satisfaction As An Intervening Variable - Egis Sugianto; Lili Karmela; Dede Djuniardi (Journal of Social Research, 2024)
Employee performance has an important role in the progress of an organization or company. Hospitals as health service institutions require optimal employee performance in providing quality services to patients. This research aims to determine the influence of work discipline, leadership style, and training on employee performance at Linggajati Regional General Hospital (RSUD), Kuningan Regency, with job satisfaction as an intervening variable. This research is descriptive research with a quantitative approach and uses survey methods. The population in this study was 226 people. Sampling in this study used the Slovin formula, a sample of 144 people was obtained with a margin of error of 5%. The data collection method uses questionnaires. The data analysis method uses SPSS and Smart PLS-SEM applications. The results of this research show that: 1). Work discipline has a positive effect on job satisfaction, 2). Work discipline has a positive effect on employee performance, 3). Leadership style has no effect on job satisfaction, 4). Leadership style has no effect on employee performance, 5). Training has no effect on job satisfaction, 6). Training has no effect on employee performance, 7). Job satisfaction has a positive effect on employee performance, 8). Job satisfaction cannot mediate work discipline on employee performance, 9). Job satisfaction cannot mediate leadership style on employee performance, 10). Job satisfaction cannot mediate training on employee performance.